COMPLICATIONS IN THE IRREGULAR USE OF POLYMETHYLMETHACRYLATE (PMMA) IN BODY HARMONIZATION - Alves, Nathaly Gabrielle Freire; Satake, Wiker Dante Fernandes; Caldeira, Kettelyn Victoria Souza; dos Santos , Mirelly Araújo Gonçalves; Almeida, Thaís Kelly da Silva; Nunes, Poliana Lucena (CIPEEX, 2025)
Introduction: Polymethylmethacrylate (PMMA) is used as a filler in aesthetic procedures, but its use is related to severe complications and has become questionable due to its non-biodegradable properties. Objective: To conduct a bibliographic study on the role of biomedical esthetes in PMMA applications, highlighting their responsibilities and importance during body aesthetic procedures. Methodology: A narrative literature search was carried out between January and March 2025, using the following keywords: PMMA. Biomedical. Aesthetic procedures. The searches were carried out in the Google Scholar database and the Regional Council of Biomedicine (CRBM 1 and 3) including scientific articles published in Portuguese and English, which addressed the professional performance in the aesthetic procedure. Results: The research showed total repudiation by the competent authorities of the CRBM/CFBM regarding the application of polymethylmethacrylate. Such a procedure is closely linked to cases of necrosis, chronic inflammation, and infections. Its non-biodegradable composition corroborates these conditions, so there is no enzyme that can degrade this substance, perpetuating it in the body. Conclusion: It is noted, therefore, that it is not a recognized, recommended or authorized practice for biomedical professionals, since they are dedicated to reaffirming their commitment to the safety, health and integrity of people. In short, the use of PMMA contradicts the CRBM guidelines, due to its side effects that bring greater harm to patients.